Porphyrinoids with Vinylene Bridges - Kuzuhara, Daiki; Yamada, Hiroko (Synlett, 2020)
Porphyrinoids containing vinylene bridges, such as triphyrin(2.1.1), porphycene, porphyrin(2.1.2.1), and hexaphyrin(2.1.2.1.2.1), are a relatively new family of porphyrinoids. Vinylene bridges give porphyrinoids a lower symmetry and a flexibility of the framework and they permit cis/trans-isomerization reactions; these factors confer unique properties to these substances, such as coordination to metal ions and aromaticity switching. In this account, the synthesis, crystal structures, and properties of new porphyrinoids containing vinylene bridges are summarized.1 Introduction2 Triphyrin(2.1.1)3 Porphycene4 Porphyrin(2.1.2.1)5 Hexaphyrin(2.1.2.1.2.1)6 Conclusion
Keywords: porphyrins; triphyrin(2.1.1); porphycene; porphyrin(2.1.2.1); hexaphyrin(2.1.2.1.2.1); vinylene bridge